THE EFFECTS OF TOURISM ON TRADITIONAL HOUSING OF BODRUM AND INHABITANTS - Nilay ÖZSAVAŞ ULUÇAY (Fırat University, 2019)
The housing structure of a city, its perception, its relationship with the environment, the living standards and effects on people are closely related. The aim of the study is to mention the traditional housing and to understand the effect of tourism on the housing structure and the user. In this study, Bodrum which is a tourism center with its geographical properties and cultural values, as well as residential typology, is addressed. Bodrum traditional housing structure is explained with examples, it is scrutinized that how it is changed by the tourism effects and what kind of problems these changes can reveal. The study includes the examples of the negative problems in tourism cities in general. In the study, interviews were made to determine the perception of the Bodrum that tourism has created on the inhabitants of the city. It is aimed to examine and understand the adverse effects of a tourism city on housing and the user with the interviews. Tourism causes structural changes in the space identity in the city by changes in the sources of economic income. In consideration of the researches and interviews, it is observed that the impact of the population density of tourism in the environment, the effect on the city and housing structure, and the changes in the environment by the tourism have the adverse effects on people. It is important to preserve the traditional tissue in cities such as Bodrum that is the center of attention for tourists not only with sea tourism but also with traditional housing structure. Researches and field works are aimed to contribute to the literature. It will be helpful for the designers to understand this process and clarify the problems.